Start-ups initiating business relationships: process and asymmetry. Issue 2 (12th June 2017) - Aaboen, Lise; Aarikka-Stenroos, Leena
Abstract : Purpose: The purpose of this paper is to develop an understanding of how start-ups initiate business relationships and to identify the subprocesses that characterise business-relationship initiations in a start-up context. Design/methodology/approach: The paper builds on business-relationship initiation models, develops a theoretical framework of relationship initiation and its subprocesses and, in a multiple-case study, applies this framework to seven relationship initiations by start-ups. Findings: The key findings of this study describe the process of business-relationship initiation by start-ups, which comprise six subprocesses. The authors' detailed and structured initiation-process analyses show how the initiation process occurs in a start-up context and how start-ups develop their relationships. The authors' analyses also reveal typical patterns and critical issues, such as asymmetry, that characterise start-ups' business-relationship initiations, particularly with bigger players. Research limitations/implications: This paper develops a model of the relationship-initiation process, uses it in a start-up context and identifies the critical characteristics, including asymmetry, of start-up initiations; these contributions address both the literature on start-ups and the literature on relationship initiation and development. Originality/value: This paper is the first to focus on how start-ups initiate business relationships; previous studies of business-relationship initiation have focussed on mature firms. Using the industrial marketing and purchasing approach, the paper contributes to shifting the focus from interactions between resource entities to relationship-initiation processes in the context of start-ups.